A Comparative Study on the Antioxidant Potentials of Hybrid and Generic Papayas Available in Jaffna, Sri Lanka - Needhiraja, N.; Chelliah, D.; Krishnamoorthy, T.; Jayasooriya, A.T.R.; Sivasinthujah, S.; Senthilnanthanan, M. (My University, 2024)
Generic papaya is a tropical plant abundant in Sri Lanka. Traditionally, it has been used therapeutically as it is a good source of polyphenols, carotenoids and an excellent source of vitamins that are powerful antioxidants. Specially, unripe fruit and leaf of papaya are recognized as a remedy for cancer and heart diseases due to their high antioxidant content. Recently, consumption of hybrid papaya fruits has increased as they are readily available in the local markets. However, the phytochemical constituents and quantity of these hybrid papaya varieties may differ from those available in the generic plant and hence their antioxidant potentials may also vary. Meanwhile there is concern within the community whether hybrid papaya has the same nutritional values as generic papaya. However, there have been no investigation done on the antioxidant activity of hybrid papaya available in Jaffna. Therefore, this study focused on investigating the in-vitro antioxidant potential of leaf and unripe fruit of generic and selected hybrid papaya varieties using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. The unripe fruits and leaves of generic and selected hybrid (Red lady, Maradona, Tanin and Vega F1) varieties were collected from the Agricultural Research and Training Centre in Jaffna, Sri Lanka. The unripe fruit was sliced after removing the skin and seeds. The sliced unripe fruit and leaves were shade dried and powdered. The powdered plant materials were macerated with methanol and ethyl acetate separately for 48 hours at room temperature. The DPPH assay was carried out on the methanol and ethyl acetate extracts of the individual plant materials by employing ascorbic acid as the standard. The obtained data were analyzed using one-way ANOVA at 5% significance level and a significant difference between the antioxidant activities of the standard (IC50 value = 12.394 μg/mL) and the selected papaya extracts (IC50 values vary from 430.641 – 6,652.267 μg/mL) was found. Further, the selected hybrid papayas exhibited better antioxidant properties than the generic one; but, did not show a common trend within them. The leaf extracts were found to possess more antioxidant potential than the unripe fruit extracts of the same papaya variety. With respect to the solvents employed in extraction, methanolic extracts of the selected papayas showed better antioxidant activity than the corresponding ethyl acetate extracts. Preliminary phytochemical screening of the leaf and unripe fruit extracts of hybrid papayas revealed the presence of alkaloids, flavonoids, polyphenols and glycosides, which could be responsible for their antioxidant activity. The finding of the study revealed that hybrid papaya could be used as a raw material for functional food as generic papaya. However, there is a need to evaluate the other nutritional values to confirm it further.